The crosstalk between sonodynamic therapy and autophagy in cancer - Zhang, Yujie; Zhao, Yuanru; Zhang, Yuanyuan; Liu, Qingguang; Zhang, Mingzhen; Tu, Kangsheng (Frontiers in Pharmacology, 2022)
As a noninvasive treatment approach for cancer and other diseases, sonodynamic therapy (SDT) has attracted extensive attention due to the deep penetration of ultrasound, good focusing, and selective irradiation sites. However, intrinsic limitations of traditional sonosensitizers hinder the widespread application of SDT. With the development of nanotechnology, nanoparticles as sonosensitizers or as a vehicle to deliver sonosensitizers have been designed and used to target tissues or tumor cells with high specificity and accuracy. Autophagy is a common metabolic alteration in both normal cells and tumor cells. When autophagy happens, a double-membrane autophagosome with sequestrated intracellular components is delivered and fused with lysosomes for degradation. Recycling these cell materials can promote survival under a variety of stress conditions. Numerous studies have revealed that both apoptosis and autophagy occur after SDT. This review summarizes recent progress in autophagy activation by SDT through multiple mechanisms in tumor therapies, drug resistance, and lipid catabolism. A promising tumor therapy, which combines SDT with autophagy inhibition using a nanoparticle delivering system, is presented and investigated.